The effect of bay leaf extract Syzygium polyanthum (Wight) Walp. on C-reactive protein (CRP) and myeloperoxidase (MPO) level in the heart of rat model of myocardial infarction - Refli Hasan; Dharma Lindarto; Gontar Alamsyah Siregar; Zulfikri Mukhtar (Medicinski glasnik, 2019)
Aim: To study the anti-inflammatory effect of bay leaf on C-reactive protein (CRP) and myeloperoxidase (MPO) level in the heart of rat model with myocardial infarction. Methods: In the first phase, results of pathological examination and biochemical assay were compared between rats with and without induction of myocardial infarction. In the second phase, the effect of bay leaf extract on CRP and MPO of rats with myocardial infarction was studied. Results: C-reactive protein and MPO were higher in rats which had myocardial infarction. Administration of bay leaf extract reduced levels of CRP and MPO in the rats started from day 4 after the induction of myocardial infarction. Conclusion: Anti-inflammatory effect of bay leaf is confirmed, reflected by decreasing of CRP and MPO levels of rat model with myocardial infarction.
Keywords: bay leaf; myocardial infarction; inflammation